Analysis of the prevalence of cervical cancer in women from the State of Piauí, Brazil (Research, Society and Development, 2020)
This is a retrospective with the objective of identifying the prevalence of cervical cancer in women in the state of Piauí through a screening carried out through data analysis at SISCOLO / MS, for the period from 2010 to 2014, being collected the epidemiological variables of the number of cases, education, age group, ethnicity, time of the exam and the type of exam, according to the chronological criterion of the attendance of women in the state of Piauí in the period from January 2010 to December 2014. Data were tabulated using Microsoft Office and Microsoft Excel 2019 and Tab for Windows (TabWin) version 4.14. Result and discussion: 5540 UCC cases were observed. The year with the highest number of cases was 2013, totaling 1469 (26.5%) notifications, and the lowest corresponded to 2014 (n = 818; 14.8%). The individuals most affected by the disease were aged between 25 and 34 years old (28.3%) and of these 29.1% had an intra-epithelial lesion under grade. The predominant ethnic group was brown (11.6%) and 12.74% of the patients had incomplete high school degree, with 80.0% and 26.0 having undergone adenocarcinoma in situ, respectively. Regarding the interval for the exam, the prevalence was 0 to 30 days (87.2%) with 95.7% invasive squamous cell carcinoma. Conclusion: It is suggested that further studies be carried out on the subject aiming to contribute significantly to the prevention of this disease, as well as serving as a contribution to the managers of public health services.